Starship troopers [videorecording (DVD)] - Neumeier, Edward; Van Dien, Casper, 1968-; Meyer, Dina, 1968-; Richards, Denise, 1971-; Busey, Jake; Harris, Neil Patrick, 1973-; Muldoon, Patrick, 1968-; Ironside, Michael, 1950-; Poledouris, Basil; Vacano, Jost; Goldblatt, Mark (Film editor); Heinlein, Robert A. (Robert Anson), 1907-1988 (Sony Pictures Home Entertainment, 2007)
A handful of dedicated young soldiers must rise to the challenge of intergalactic warfare with a species of terrifying alien insects that threaten to eliminate the human race.